Women's preference for dominant male odour: effects of menstrual cycle and relationship status - Havlicek, Jan; Roberts, S Craig; Flegr, Jaroslav (Biology letters, 2005)
Body odour may provide significant cues about a potential sexual partner's genetic quality, reproductive status and health. In animals, a key trait in a female's choice of sexual partner is male dominance but, to date, this has not been examined in humans. Here, we show that women in the fertile phase of their cycle prefer body odour of males who score high on a questionnaire-based dominance scale (international personality items pool). In accordance with the theory of mixed mating strategies, this preference varies with relationship status, being much stronger in fertile women in stable relationships than in fertile single women.
Keywords: zdravotní stav; Genetic Variation; fertilita; Sexual Behavior; sexuální chování; analýza rozptylu; Reproduction; ženské pohlaví; lidé; Fertility; menstruační cyklus; mužské pohlaví; rozmnožování; Menstrual Cycle; Analysis of Variance; Humans; Health Status; Odorants; odoranty; Female; genetická variace; Male